Appropriate for Alternative Agricultural System Management and Mechanism of Participation in the area of Land Readjustment, Kamalasai District, Kalasin Province - Saranrom, Ponsaran; Thongchure, Siros; Onsumrarn, Wattanai (Journal of Vocational Education in Agriculture, 2023)
The objectives of this research were to study 1) context in agricultural system management of farmers in the land readjustment area, 2) appropriate alternative agricultural system management in the land readjustment area, and 3) mechanism of participation in the operation of the appropriate agricultural system in the land readjustment area. The population in this study were 1) 595 farmers living in the area of Lam Pao Operation and Maintenance project. The sample size of 86 people was determined using Taro Yamane formula at 0.10 level of error and simple random sampling method. The structured interview was used to collected data regarding the context of agricultural system management and data were analyzed using descriptive statistics; 2) key informants on the alternative agricultural system and mechanism of participation which was selected by purposive sampling comprised of ten farmers, ten agricultural entrepreneurs, one district agricultural extension officer, and 7seven agricultural scholars in the university. The form of survey, in-depth interview, opinion’s evaluation and focus group discussion were used to collect data and the data were analyzed using content analysis. The results of this study revealed that 1) regarding agricultural management context, it showed that all of the farmers mainly produced rice with the average productivity of 571.09 kilogram/Rai, the average income of 4,098.37 Baht/Rai, and the average deficit of 256.51 Baht/Rai) the appropriate for alternative agricultural system in the land readjustment area was divided into four systems including (1) rice mono-cropping system (2) crop rotation such as rotation rice production with peanut production (3) rice production system along with other agricultural activities for examples, rice production with vegetable production, herbs, cultivated banana, mango, custard apple, local chicken breed, and beef cattle and (4) integrated farming system. The evaluation of opinion regarding the appropriate for alternative agricultural system in the land readjustment area indicated that most opinions in terms of suitability, possibility and usefulness were all at high level. 3) mechanism for participation had two levels which were (1) activity network mechanism of the community in the project area and (2) mechanism of committees driving comprehensive agricultural development.